Impact of Agricultural Production on Rural Welfare in Nigeria (2012)
Increase in agricultural production is essential for agricultural development since it enhances profitability and income which leads to welfare improvements. In Nigeria agricultural production and rural welfare have worsened over the years. Adequate information on the link between agricultural production and rural welfare in Nigeria is expected to better inform policy makers on implementation. Agricultural production and its impact on rural welfare in Nigeria were, therefore, investigated. Secondary data covering the military period (1970-1979 and 1984–1999) and democratic (1980–1983 and 1999-2007) periods were used for the study. The pre-Millennium Development Goals - MDGs (1970– 1999) and MDGs (2000–2007) periods also fall within the study period (1970 – 2007). The government regimes (military and democratic) as well as the pre-MDGs and MDGs periods captured the various policies implemented. Data were obtained from the National Bureau of Statistics (NBS), Central Bank of Nigeria and the Food and Agriculture Organization. Data were extracted on agricultural inputs and production, Agricultural Gross Domestic Product (AGDP), foreign private investments in agriculture, agricultural budgets as well as infrastructural and industrial development indices. These were analysed against extant policy regime at the periods of data collection. Rural welfare was proxied by real AGDP per capita. Data were analysed using descriptive statistics, stochastic frontier function and generalized method of moments at p = 0.05. Irrigated area as a percentage of arable land was highest in the MDGs period (0.90±0.03) and lowest during the pre-MDGs period (0.74±0.04). Use of tractors per ha of arable land was highest during the MDGs (9.74±0.64) and lowest at pre-MDGs era (5.78±3.08). Rate of fertilizer use was highest (15.51±3.47) during the democratic period and lowest during military rule (13.34±3.46) kg ha-1. Aggregate index of agricultural production peaked during the MDGs period (165.5814.85). Production indices for crop, livestock, and forestry were highest during the MDGs period (176.58±22.53, 225.91±36.54, and 129.42±11.89) but that of fishery peaked during the democratic period (158.62±29.79). The AGDP as a percentage of national GDP was highest during the MDGs period (41.76%) and lowest during the pre-MDGs period (38.72%). Agricultural budget as a percentage of total national budgets was highest during the military period (3.67±2.77) and lowest during the democratic period (3.21±2.87). Improvement on road was highest during the military era (63.00±26.51) while industrial development peaked during the democratic period (53.83±11.47). Percentage of foreign  private investments in agriculture peaked during the pre-MDGs (1.77±1.03). A unit change in area under irrigation led to increase in agricultural productivity by 2.11%. Agricultural productivity index was highest during the MDGs period (0.87±0.09) and lowest during pre-MDGs era (0.84±0.11). Real AGDP per capita was also highest during the MDGs era (N2872.19±491.75) and ebbed during military era (N1950.75±398.76). Agricultural productivity and agricultural budgets significantly improved rural welfare by 0.28% and 0.29%. Also, industrial development and road infrastructure indices significantly improved rural welfare by 0.01% and 0.11%. The policies implemented during democratic period significantly improved rural welfare by 0.65%. Increase in agricultural production led to significant improvement in rural welfare in Nigeria. Increment in land area under irrigation would therefore, be recommended to sustain the agricultural production